Economic viability of large-scale production of the biocontrol agent Trichoderma harzianum Rifai - M Anandaraj, R Suseela Bhai, I S Meera, M S Madan, K V Ramana, K A Manoj, (Journal of Spices and Aromatic Crops, 2006)
The economic viability of large scale production of the biocontrol agent Trichoderma harzianumeffective against the soil-borne disease Phytophthora foot rot (caused by P. capsici) of blackpepper (Piper nigrum) was studied. The enterprise was highly profitable for the entrepreneurwith a benefit:cost ratio of 1.84. The investment returned a net present worth of Rs. 2,42,618@ 11% interest rate for 10 years period with an internal rate of return of 121%.